Potential of the parabolic trough collectors use in the industry of Cyprus: Current status and proposed scenarios - Ktistis, Panayiotis K.; Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2018)
Cyprus is the worldwide leader country for the use of solar water heating systems per capita, which are of the thermosiphon solar water heating type. In this paper, an investigation of the perspective to start using parabolic trough collectors (PTC) is carried out. The idea to use PTC systems is still new in Cyprus since there are no installations and it is not a well-known technology yet, but it could create a good prospect by starting from the large industries of the island. Although the industrial market of Cyprus is small, the large amount of incident solar radiation throughout the year and the need of the people to reduce their energy needs, makes the idea to adopt PTC collectors for energy production very tempting. Most of the industries use thermal and electrical energy for their various processes, with the biggest consumer to be the nonmetallic minerals industry (glass, pottery and building materials) and the second bigger consumer the food industry. The latter requires large amount of thermal energy which could be provided by PTC since the required temperatures are 120°C - 250°C which is very common range of temperatures for such systems. Thus, parabolic trough collector systems could be a sustainable, profitable and dispatchable technology, especially for the Cypriot industries. This study presents an investigation carried out to summarize the current status of the industrial energy needs as well as the systems being used for energy production currently. Accordingly, an examination of the PTC systems is done in order to identify the potential of installation of such a system in a case study from the industrial sector, considering the energy production, the cost of installation and cost of energy savings as well as the CO2 emissions reduction. Finally, a discussion is made on the potential of the Cypriot industry to use PTC collectors analyzing the pros and cons of such applications.
Keywords: Parabolic; PTC; Industry; Thermal Energy; TRNSYS